Fenomena Diskriminasi Sosial dalam Film Yuni Karya Kamila Andini : Kajian Sosiologi Sastra - Komariyah Komariyah; Ghufroni Ghufroni; Hanny Uswatun Nisa (Peneliti.net, 2022)
This study aims to describe the form of social discrimination experienced by the main character of Yuni's film, describe the factors causing social discrimination of the female protagonist in Yuni's film, describe the response of the main character in Yuni's film in resisting the acts of social discrimination she experienced. The method used in this study is descriptive qualitative. The object in this study is a film with the title Yuni. This research focuses on problems related to social discrimination that afflicts female characters in Yuni's films by reviewing using literary sociological studies. Data retrieval techniques by watching movies thoroughly and recording findings. The validity of the data is obtained through semantic validation and reliability. The results obtained from this study show that (1) The most dominant form of discrimination is the form of public discrimination in the form of ridicule, gender discrimination and social discrimination experienced by female characters in films. (2) The factors causing social discrimination in the domestic sphere are gender factors, while in the public domain, namely religious factors, and social strata factors. (3) The most dominant response is the response of refusing to be manifested in the form of verbal actions and the writing of a certain thing or opinion.